Parametric optimization of surface dielectric barrier discharge actuators for ice sensing application - Abdollahzadehsangroudi, Mohammadmahdi (2022)
In this paper a parametric optimization of the dielectric barrier discharge (DBD) plasma actuator is con ducted in order to achieve better ice sensing and deicing performance. For this purpose, different DBD plasma actuators were tested by changing the main geometrical dimension of the DBD plasma actuator and dielectric material. Both the ice sensing and thermal characteristics of the DBD plasma actuator were analyzed and compared. The results reveal that there exists two separate set of optimum parameters that lead to best ice sensing and thermal behavior. For both the sensing and thermal characteristics, the thinnest DBD showed the best performance. Kapton DBD plasma actuator showed the highest surface temperature while PMMA (poly methyl methacrylate) had the best performance for ice sensing. In the end, the deicing performance of a DBD actuator that had in average better thermal and ice sensing performance was tested for deicing an ice layer and a frost layer. The progress of the deicing process and the ice sensing measure on the surface were recorded and analyzed.